Evaluación Financiera Del Plan De Negocio Para La Siembra y Comercialización De Heliconias, En El Corregimiento De Minca Sierra Nevada De Santa Marta En 2020 (2020)
This work aims to publicize the financial viability and commercialization of various types of heliconias in the Minca Sierra Nevada area in Santa Marta, these are exotic flowers of great preference today both for hotels and for event houses and florists. Related aspects such as their acceptance when acquired in the market, the description of the plant and its floral biology are analyzed. In addition, the production area is evaluated, since this crop needs specific conditions, as well as the necessary cultural attentions to achieve better quality in production to be able to leave a mark with the brand, a demand projection is also made throughout the years that allow a permanent consolidation of the company and that allows it to broaden its horizons when it comes to growth; Finally, a financial plan is implemented to support the entire project when it is executed and thus determine the annual profitability of production.